Eco rabbit’s delivery box / Muhammad Danish Rayyan Muhammad Rahmat … [et al.] - Muhammad Rahmat, Muhammad Danish Rayyan; Md. Rohani, Norhafida; Muhammad, Nur Syuhada; Muhammad Rahmat, Nur Umaira Darina; Muhammad Rahmat, Muhammad Luqmanul Hakim; Abas, Aemillywaty (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
As the cuniculture industry is growing, more rabbit trading takes place between rabbits’ sellers and buyers. Some of the buyers are willing to travel long distances just for the purpose of buying rabbits that they are interested of. After the purchase takes place, buyers will transport back the rabbits to their hometown, however, the transportation of a rabbit requires significant responsibilities and extra care because rabbits, being a flight/prey species can be stressed very easily. Rabbits can get seriously ill from the stress of long-distance travel. It can cause them to go into Gastrointestinal Stasis, a condition that affects the rabbit’s digestive system and subsequently causes their body to begin to shut down (Yorston, M., 2013). During transportation, rabbits need to be fed, watered, given an opportunity to rest, and protected from injuries. Therefore, in preparing for a delivery box, the seller has to prepare a sufficient amount of feed in advance and it must be specially adapted with drinking equipment as to keep the rabbits alive and healthy. Recognizing this need, Eco Rabbits’ Delivery Box is created to help rabbits de-stress and remain comfortable, full and healthy during a long period of travel. Besides that, the materials used for this delivery box is also recyclable and compostable. Super Napier grass is a high-yielding green fodder and is very good and nutritious for rabbits. Besides yield, Super Napier has crude protein ranging from 17 to 18 percent. It is very palatable because the stalks are tender. The leaves are smooth and hairless, and animals love to eat them as its juice is sweetish (Rehoboth Organic Farms, 2022). Therefore, Napier Grass and water are the two most important elements in this box which keep the rabbits happy, full and healthy during their transportation period.